PENGARUH KDS SITUBONDO TERHADAP DAYA TARIK KONSUMEN DALAM KEPUTUSAN PEMBELIAN BERBELANJA FASHION PADA BULAN RAMDAHAN - Nanik Hariyana (Relawan Jurnal Indonesia, 2019)
Based on the above understanding, it can be concluded that the shopping center is a commercial building complex that is designed and planned along with retailers and supporting facilities to provide comfort in the trading activities that it holds. Trade activities in this modern shopping center are not accompanied by bargaining on goods such as traditional markets. A modern shopping center is a shopping center with a self service system or serviced by a salesperson, selling various types of goods in retail. Modern shopping centers usually consist of tenants who are rented to businesses and anchor tenants in the form of Situbondo peer support groups or supermarkets